Aktivitas Antibakteri Infusa Daun Mangga Bacang (Mangifera foetida) Terhadap Bakteri Aeromonas hydrophila - Cahya Ningsih, Ayu; Roka Aji, Oktira (Universitas PGRI Palembang, 2025)
Aeromonas hydrophila is an infectious agent that triggers Motile Aeromonas Septicemia (MAS) in freshwater fish, including catfish, leading to significant economic losses in aquaculture. This study aims to evaluate the antibacterial activity of Mango Bacang (Mangifera foetida L.) leaf infusion against A. hydrophila and its effect on catfish mortality. The research methods included the preparation of the infusion, phytochemical screening, antibacterial activity testing, and assessing the infusion's impact on catfish mortality. Phytochemical screening revealed that Mango Bacang leaf infusion contains alkaloids, flavonoids, phenols, tannins, and saponins, contributing to its antibacterial properties. The well-diffusion technique used to examine antibacterial effects demonstrated that the infusion at concentrations of 5–100% produced significant inhibition zones against A. hydrophila, with strong activity observed at a 5% concentration (14.38 ± 1.67 mm). However, toxicity testing on catfish indicated increased mortality with higher infusion concentrations, reaching 50% at 5% concentration. These findings suggest that Mango Bacang leaf infusion has potential as a natural antibacterial agent to control A. hydrophila, but its use requires precise dosage management to ensure safety for catfish. Further studies are necessary to optimize effective and environmentally friendly concentrations and explore applications on a broader scale.